Pengaruh Corporate Sustainability Performance terhadap Corporate Financial Performance dengan Karakteristik CEO sebagai Variabel Moderasi - Arianti, Yessy Dwi; Pebriyani, Dewi (Universitas Negeri Padang, 2025)
This study aims to examine the effect of corporate sustainability performance on Corporate financial performance with CEO characteristics as a moderating variable. Corporate sustainability performance is an independent variable and corporate financial performance as the dependent variable, while CEO characteristics as a moderating variable are proxied by CEO tenure and CEO education level. This research was conducted at mining sector companies listed on the Indonesia Stock Exchange in 2020- 2022, with a total sample of 21 companies. The sampling method used in this study is purposive sampling method with criteria and requirements that have been adjusted to the research needs. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that corporate sustainability performance has a positive effect on corporate financial performance. While the CEO characteristics variable proxied by CEO tenure and CEO educational background has not been able to moderate or strengthen the effect of corporate sustainability performance on corporate financial.